2015
DOI: 10.1123/ijsnem.2013-0174
|View full text |Cite
|
Sign up to set email alerts
|

Doping Through Supplement Use: A Review of the Available Empirical Data

Abstract: The potential for supplement use to result in doping infringements is likely to be of concern for anyone involved in sports nutrition. The available data indicates that between 40-70% of athletes use supplements, and that between 10-15% of supplements may contain prohibited substances. Such data indicates that there is a considerable risk of accidental or inadvertent doping through using supplements. Accordingly, this paper sets out to provide an overview of the currently available empirical evidence of accide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 15 publications
0
63
0
6
Order By: Relevance
“…Given the risk of supplement contamination and the potential for failed drug tests [118] supplements are now often only given when there is a clear rationale for their use combined with the availability of independently drug-tested products. It is beyond the scope of this review to cover all supplements therefore the most popular ones are categorized according to the level of evidence supporting their benefit and summarized in Table 1.…”
Section: Traditional Sports Supplements -The Ones That Still Work In mentioning
confidence: 99%
“…Given the risk of supplement contamination and the potential for failed drug tests [118] supplements are now often only given when there is a clear rationale for their use combined with the availability of independently drug-tested products. It is beyond the scope of this review to cover all supplements therefore the most popular ones are categorized according to the level of evidence supporting their benefit and summarized in Table 1.…”
Section: Traditional Sports Supplements -The Ones That Still Work In mentioning
confidence: 99%
“…Na verdade, do ponto de vista clínico, isso seria interessante, uma vez que a suplementação pode beneficiar atletas com deficiências nutricionais pré-existentes e sob dietas hiper ou hipocalóricas 4,8,12 . No entanto, há de se considerar que 10 a 15% dos suplementos contém substâncias proibidas e apresentam considerável risco de doping acidental ou involuntário 40 33 revisou o tema suplementos alimentares e modalidades coletivas. A presente revisão sistemática além de ter investigado a prevalência e características do consumo dos suplementos, também abordou os fatores associados a esse consumo, e também estendeu a atletas de diversas modalidades e qualquer faixa etária.…”
Section: Discussionunclassified
“…The use of substances for improving performance began to be considered inappropriate after the war, and the first doping tests were introduced in sports in the 1960s 17,24 .…”
Section: From Where We Comementioning
confidence: 99%
“…Some problems have been identified with this practice -a study showed that the type of supplement used and the reasons for its use are not always congruent, indicating athletes' insufficient knowledge on the topic 46 . Even worse is the fact that 10.0-15.0% of nutritional supplements may be tampered with substances that can be considered doping agents 24 . Outram & Stweart 24 estimate that 6.4 to 8.8% of the identified doping cases can be attributed to the use of these supplements.…”
Section: Eating Habits Of Athletes and Their Ways Of Eatingmentioning
confidence: 99%
See 1 more Smart Citation